Molecular cytogenetic delineation of a novel critical genomic region in chromosome bands 11q22.3-923.1 in lymphoproliferative disorders. - Stilgenbauer, Stephan; Liebisch, Peter; James, Michael R.; Schröder, Martin; Schlegelberger, Brigitte; Döhner, Konstanze; Bentz, Martin; Lichter, Peter; Döhner, Hartmut (Proceedings of the National Academy of Sciences of the United States of America, 1996)
Aberrations of the long arm of chromosome 11 are among the most common chromosome abnormalities in lymphoproliferative disorders (LPD). Translocations involving BCL1 at 11q13 are strongly associated with mantle cell lymphoma. other nonrandom aberrations, especially deletions and, less frequently, translocations, involving bands 11q21-923 have been identified by chromosome banding analysis. To date, the critical genomic segment and candidate genes involved in these deletions have not been identified. In the present study, we have analyzed tumors from 43 patients with LPD (B-cell chronic lymphocytic leukemia, n = 40; mantle cell lymphoma, n = 3) showing aberrations of bands 11q21-923 by fluorescence in situ hybridization. As probes we used Alu-PCR products from 17 yeast artificial chromosome clones spanning chromosome bands 11q14.3-923.3, including a panel of yeast artificial chromosome clones recognizing a contiguous genomic DNA fragment of approximately 9-10 Mb in bands 11q22.3-923.3. In the 41 tumors exhibiting deletions, we identified a commonly deleted segment in band 11q22.3-923.1; this region is approximately 2-3 Mb in size and contains the genes coding for ATM (ataxia telangiectasia mutated), RDX (radixin), and FDX1 (ferredoxin 1). Furthermore, two translocation break-points were localized to a 1.8-Mb genomic fragment contained within the commonly deleted segment. Thus, we have identified a single critical region of 2-3 Mb in size in which 11q14-923 aberrations in LPD cluster. This provides the basis for the identification of the gene(s) at 11q22.3-923.1 that are involved in the pathogenesis of LPD.
Gesehen am 04.11.2024